Implementation of Precautionary Principles in Environmental Impact Assessment (EIA) in Indonesia - Cahyani, Ferina Ardhi; Anditya, Ariesta Wibisono (Unifikasi : Jurnal Ilmu Hukum, 2024)
This study aims to thoroughly examine the implementation of precautionary principles in environmental impact assessment (EIA). In order to achieve the stated objective, a socio-legal study method was adopted. The obtained results showed that in the context of environmental approval requirements in Indonesia, EIA remained a key requirement. Typically, in the process of preparing, implementing, monitoring, and evaluating certain activities to be carried out, the principle of caution is ensured to be upheld optimally. This principle is often introduced to ensure that all projects permitted by the government do not pose a propensity to harm the community. In EIA process, there is an obligation to examine the opinions of individuals who could be directly affected by an activity before its implementation. Despite the effectiveness of this approach, it was observed to still possess certain weaknesses. This includes the fact that even after EIA has passed the assessment phase, continuous monitoring and evaluation are still necessary. The government must ensure that any risks associated with an activity are identified and addressed.